A structural crack monitoring gasket for aircraft bolt-jointed structures with temperature compensation. (4th October 2018) - Chen, Tao; Du, Jinqiang; He, Yuting
Abstract: In order to meet the need of the quantitative monitoring of cracks in critical connection structures of aircraft, aiming at improving the durability of sensors and the reliability of signals, a structural crack monitoring (SCM) gasket, which can be used for the quantitative monitoring of cracks in bolted joints, is developed. The gasket is formed by a gasket substrate and a flexible eddy current sensor integrated to withstand the load, with the capability of temperature compensation. First of all, a new temperature-compensated rosette eddy current array (TC-RECA) sensor is designed and used to study the failure mode of the sensor. According to the failure mode of the sensor, a gasket substrate with load-bearing capacity is developed. Subsequently, the influence of permeability, conductivity and lift-off on the trans-impedance of the sensor is studied. The influence of permeability on the trans-impedance is characterized by conductivity. Based on this, a temperature compensation method for ferromagnetic materials is developed. Then, a temperature influence experiment and a structural crack quantitative monitoring experiment are carried out using a front beam connection structure of an aircraft wing. The temperature effect experimental results show that even if the ambient temperature changes from 60 °C to −40 °C, the characteristic signal Δ C does not change significantly, indicating that the gasket has a temperature compensation capability. The experimental results of the crack monitoring of the front beam connection structure show that the gasket can bear the load and has the capability to quantitatively monitor cracks, and can be used for the quantitative monitoring of cracks in the critical connection structure of aircraft structures.